PENGARUH PENERAPAN LEMBAR KERJA SISWA BERBASIS KETERAMPILAN PROSES SAINS TERHADAP DAYA NALAR DI KELAS XI SMAN 3 PAYAKUMBUH - Sri Wahyu Hidayati; Pakhrur Razi; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2015)
Reasoning ability is needed in life as a basis for solving the problems of life. One effort that can be done to develop the learners reasoning is apply science process skills. The implementation of this skill has a purpose so that learners are able to seek and find their own answers or the various problems faced by holding a series if science process skills. Therefore, researchers compiled Physics worksheets using existing skills in science process skills. This research aims to determine the effect of the application of worksheets based on science process skills to the reasoning power of students in grade XI of SMAN 3 Payakumbuh. The kind of this research i a quasi experimental design with a randomized control group design only, with a population of eleventh grade students of  SMAN 3 Payakumbuh enrolled in the academic year 2013/2014. The sampling technique used was purposive sampling. The sample is XI IPA 4 as a experiment XI IPA 5 as the control class. The research data is the ability of reasoning power of Physics students. The research instrument is the achievement test. Based on the analysis of data obtained by the average power of reasoning experimental class is 68.86 which is at sufficient category and the average ability of reasoning power control class 62.99 in middle category. The data obtained were analyzed using two common test average through to test. Conclusion of this research is the hypothesis that there is a significant impact on the use of science process skills worksheets based on the power of reason in grade XI of SMAN 3 Payakumbuh be accepted on the real level of 0.05. Thus, the use of science process skills worksheets can improve students’ reasoning